2010
DOI: 10.1186/1471-2164-11-s2-s9
|View full text |Cite
|
Sign up to set email alerts
|

Speckle reducing bilateral filter for cattle follicle segmentation

Abstract: BackgroundUltrasound imaging technology has wide applications in cattle reproduction and has been used to monitor individual follicles and determine the patterns of follicular development. However, the speckles in ultrasound images affect the post-processing, such as follicle segmentation and finally affect the measurement of the follicles. In order to reduce the effect of speckles, a bilateral filter is developed in this paper.ResultsWe develop a new bilateral filter for speckle reduction in ultrasound images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Its principal virtues have widely been recognised in 2D image processing [9,12,13] and, more recently, in medical imaging as well [2-6], but applications in Nuclear Medicine in general and PET in particular seem to have been missing up to now (we have found only one exception [14], where BF was mentioned as a preprocessing step for a new image segmentation algorithm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its principal virtues have widely been recognised in 2D image processing [9,12,13] and, more recently, in medical imaging as well [2-6], but applications in Nuclear Medicine in general and PET in particular seem to have been missing up to now (we have found only one exception [14], where BF was mentioned as a preprocessing step for a new image segmentation algorithm).…”
Section: Discussionmentioning
confidence: 99%
“…Such filters are typically used in 2D image processing and were first introduced by Tomasi and Manduchi [1]. BF have already been used in medical imaging, notably in MRI [2-4] and ultrasound imaging [5,6]. Their potential usefulness has also been recognised in the field of Nuclear Medicine [7], and bilateral filtering has been proposed for improvement of iterative image reconstruction in PET [8].…”
Section: Introductionmentioning
confidence: 99%
“…The other filter operates in the intensity domain, where the filtering weight is calculated based on the difference between the intensity values of the origin pixel and those of its neighboring pixels. Tang et al analyzed the behavior of filtering in the intensity dimension of a conventional bilateral filter for multiplicative noise 4 . He found that the intensity difference between two pixels was not only related to the difference of the noise but was also related to the intensity of the pixels in the homogeneous region of speckle-corrupted images.…”
Section: Normalized Bilateral Filtermentioning
confidence: 99%
“…Bilateral filters, another type of popular nonlinear filters, have received a lot of attention in terms of speckle reduction recently due to their ability to suppress noise suppression and preserve edges 3 . Tang et al modified a conventional bilateral filter by introducing a normalized difference in the intensity domain 4 . The filter developed by Tang et al 4 , referred to as a normalized bilateral filter, can be directly applied to speckle reduction in ultrasound images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation